Robust fault detection filters design for switched systems with all subsystems unstable. Issue 4 (17th January 2019) - Su, Qingyu; Fan, Zhongxin
Abstract: This paper studies the fault detection problem for switched systems with all modes unstable. In this paper, we convert the fault detection filters design problem into the H ∞ performance study. First, employing the average dwell time approach, a switching signal ensuring the stability property is acquired. Then, through discretized Lyapunov function method, a novel Lyapunov function is put forward. In addition, sufficient conditions are presented to get the H ∞ performance in terms of LMIs. It should be mentioned that the parameters of the fault detection filters can be gained through solving the LMIs, utilizing the Schur's lemma. Finally, an example is given to show the effectiveness of the proposed method.